2007
DOI: 10.1080/09593960701189903
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing for overseas private labels: A win–win strategy for retailers and producers

Abstract: The study discusses the use of private labels, both for retailers and manufacturers, within the context of international markets. It is proposed that agreements between manufacturers and retailers from different markets may solve or mitigate some abiding frictions and serve the interest of both parties. Using data collected through 101 in-depth interviews among marketing managers, qualitative and quantitative procedures were used to explore producers' attitudes and behaviour in regard to agreements to manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, many studies in the literature have suggested that national brand manufacturers and market leaders refrain from producing private brands for economic-financial (unsatisfactory profitability), competitive (cannibalization), and relational (poor guarantee of contract duration) reasons (Gómez & Benito, 2008;Timmor, 2007). For manufacturers, instead of completely ignoring the potential, they should identify and carefully evaluate private brand opportunities in terms of market and product characteristics, and then find ways to collaborate with retailers to increase sales growth and improve profitability (Scaff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies in the literature have suggested that national brand manufacturers and market leaders refrain from producing private brands for economic-financial (unsatisfactory profitability), competitive (cannibalization), and relational (poor guarantee of contract duration) reasons (Gómez & Benito, 2008;Timmor, 2007). For manufacturers, instead of completely ignoring the potential, they should identify and carefully evaluate private brand opportunities in terms of market and product characteristics, and then find ways to collaborate with retailers to increase sales growth and improve profitability (Scaff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…When private brands were first introduced, manufacturers did not view them as a threat to their own national brands because many consumers were skeptical of the quality of private branded products given their lower cost. Manufacturers did not view private branded products as an attractive alternative to national brands because their production often created negative effects on the value perception of their own national brands and profitability (Timmor, 2007).…”
Section: Introductionmentioning
confidence: 99%